Hormonal changes in high altitude residents - Antezana, Ana Maria; Richalet, Jean Paul; Antezana, Gerardo; Carreon, R. (Acta Andina, 2025)
The response of renin and aldosterone: is attenuated under acute and chronic exposure to high altitude (HA); the release of atrial natriuretic peptide (ANP) in sea level (SL) natives is also modified. No data are available in HA residents in whom increased total blood volume and the pulmonary arterial hypertension may influence the hormonal release. Twenty four men residing at 3600 ± 200m, La Paz, were included either in a normocythemic group "HAN" (hematocrit, Ht <57%, n= 13) or in a polycythemic group "HAP" (Ht> 57%, n= 11). A control group of SL residents was studied in normoxia "SLN" and at 4,350m "SLH". Plasma active renin, aldosterone, ANP, potassium and norepinephrine concentrations were measured at rest and after a maximal exercise. Pulmonary artery pressure was assessed by Doppler at rest. In SLH, renin and aldosterone were blunted, and ANP was unchanged. In highlanders, the renin response was normal in HAN but decreased in HAP. The exercise-induced increase in aldosterone was lower in HA natives than in SL natives. The correlation between renin and aldosterone observed in SLN and HAN was not found in the group HAP. A protective mechanism against water and salt retention in polycythemic subjects may be evoked. ANP in highlanders was lower than in SL natives. Lower ANP in HA residents in spite of higher pulmonary pressure could be an adaptation to chronic distension of atrial stretch receptors.